Screening and treatment of patients with breast diseases in practice of obstetrician-gynecologist - T V Ovsyannikova (Гинекология, 2017)
The article presents the program and stages of breast examination in patients seeking an obstetrician-gynecologist. The classification of benign breast diseases (BBD), the possibility of treatment of gynecological diseases with dyshormonal pathology and the effectiveness of this therapy in mastitis and mastodynia. Submitted by the products developed and registered for the treatment of BBD. Attention is paid to drug Mastodynon possessing a multifaceted effect on various parts of the endocrine system in the treatment of premenstrual syndrome, defective lutein phase, mastitis and mastodynia.